Implementation of Occupational Health and Safety during the Covid-19 Pandemic at Dadapayam Puskesmas - Meliana Novita; Agus Sugiarto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Occupational Health and Safety (K3) is a program created for workers or laborers as well as employers as a form of prevention of work accidents and occupational diseases that may occur to workers in the work environment. The purpose of this study was to analyze the implementation and barriers and challenges of occupational safety and health at the Dadapayam Health Center during the Covid-19 period. The method used is descriptive with a qualitative approach. Data collection techniques were carried out by means of observation, interviews and also documentation studies. Data analysis activities are carried out through the stages of data condensation, data presentation, and drawing conclusions. The results showed that the Dadapayam Health Center had implemented occupational safety and health (K3). In the process of implementing K3 during the Covid-19 period, the initial steps and stages of K3 planning were quite good and in accordance with applicable regulations. However, there are obstacles and challenges that have in the process of implementing occupational safety and health during the Covid-19 period being slightly disrupted and not functioning optimally. The implication of the implementation and obstacles at the Dadapayam Health Center during the Covid-19 period is to provide more knowledge to the community, especially to health workers who work at the Dadapayam Health Center so that they continue to apply K3 in every daily activity.